Hubungan antara perfeksionisme dengan kesehatan mental pada remaja: Tinjauan berdasarkan teori psikoanalitik Sigmund Freud - Rahma, Resa Kurnia (Maliki Interdisciplinary Journal, 2025)
Perfectionism is an individual's tendency to demand perfection in every aspect of life, which often causes severe psychological pressure, including for adolescents. In the context of psychology, perfectionism can be seen as a manifestation of personality dynamics described in Sigmund Freud's psychoanalytic theory, in which the conflict between the ego and the superego tends to affect a person's mental stability. This article aims to examine the relationship between perfectionism and adolescent mental health through a psychoanalytic approach, with a primary focus on intrapsychic factors and sociocultural influences. This study uses various relevant scientific journals as the basis for its literature review method. Based on the analysis results, unhealthy perfectionism is associated with increased levels of anxiety, stress, and depression in adolescents. This is influenced by pressure from the superego, which demands excessive idealism, as well as the ego's inability to balance these demands with reality. In the context of Indonesian adolescents, this phenomenon is further reinforced by academic pressure, family expectations, and the influence of social media, which normalizes standards of perfection. This study emphasizes the importance of understanding psychoanalytic aspects in understanding adolescent mental health and provides direction for more in-depth psychological interventions oriented towards personality balance.